Characterization and functional capacity in women with breast cancer, gynaecological cancer and gestational trophoblastic disease - Thaís Cristina Elias; Lorena Campos Mendes; Maurícia Brochado Oliveira Soares; Sueli Riul da Silva
Objective: to describe the social, demographic and clinical profile, and functional capacity of women diagnosed with gynecological cancer, breast cancer and gestational trophoblastic disease during chemotherapy. Method: longitudinal retrospective study that evaluated the records of women treated in hospital clinics from January 2000 to December 2012. Results: they evaluated the records of 438 women. The analysis showed that were not able to perform their daily activities, limited to the activities of self-care. Older patients had greater functional impairment during therapy. Conclusions: the sample was women 41 to 50 years, diagnosed with breast cancer (50.9%) and made use of anthracycline based protocols (47%); the scores of the functional capacity of the sample fell from 78.22 to 73.57. It is evident that nursing care should focus on the control of signs and symptoms that impact the functional capacity of women under chemotherapy.